Economic Growth and the Rise of Forests - Foster, A. D.; Rosenzweig, M. R. (Quarterly Journal of Economics, 2003)
Although forests have diminished globally over the past 400 years, forest cover has increased in some areas, including India in the last two decades. Aggregate time-series evidence on forest growth rates and income growth across countries and within India and a newly assembled data set that combines national household survey data, census data, and satellite images of land use in rural India at the village level over a 29-year period are used to explore the hypothesis that increases in the demand for forest products associated with income and population growth lead to forest growth. The evidence is consistent with this hypothesis, which also shows that neither the expansion of agricultural productivity nor rising wages in India increased local forest cover.